AZT sensitizes hepatocellular carcinoma cells to As2O3 by upregulating the arsenic transporter aquaglyceroporin 9 - Wang, Mei; Liang, Yongjuan; Zhao, Chuan; Wang, Xiuyue; Chen, Che (Translational Cancer Research, 2018)
Background: Even though the mechanism is unknown, previous studies have demonstrated that the traditional chemotherapy agents, 3'-azido-3'-deoxythymidine (AZT) and arsenic trioxide (As2O3), can synergetically inhibit the growth, migration and the invasion of hepatocellular carcinoma cells. This study aimed to investigate the role which aquaglyceroporin 9 (AQP9), an arsenic channel protein which is widely distributed in the liver tissues, plays in the process of As2O3 combined with AZT in inhibiting growth, migration and the invasion of hepatocellular carcinoma cells. Methods: HepG2 and MHCC97H cells were treated using As2O3 (2 µM) combined with a wide range of different concentrations of AZT (0, 10, 20 µM) for 48 h, and the proliferation inhibition rates were detected using a MTT assay. AQP9 mRNA/protein expression was determined by RT-PCR and western blotting assays, respectively. Next, HepG2 cells were electro-transfected with AQP9 siRNA to disturb the expression of AQP9, which was verified by RT-PCR and western blotting. The effect of the 2 µM As2O3 combined with 20 µM AZT (the optimum synergy inhibition concentration investigated previous) on the migration and invasion of HepG2 cells was then measured by wound healing assay and transwell migration assay and invasion assays, respectively, before and after an AQP9-siRNA transfection. Results: The proliferation inhibition rate from the combination of As2O3 and AZT on the hepatocellular carcinoma cells was significantly higher than the rate from As2O3 alone (P